2013
DOI: 10.1007/s00415-012-6814-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio of multiple sclerosis in persons born from 1930 to 1979 and its relation to latitude in Norway

Abstract: A remarkable increase in female to male ratio of multiple sclerosis (MS) is recognised in high incidence areas. Norway is a high-risk area for MS, spanning latitudes 58-71 °N. We studied whether the sex ratio has changed over time and whether it differs by clinical phenotype or by latitude. Population-based epidemiological data and data from the Norwegian MS Registry on patients born from 1930 to 1979 were combined in this study. Place of birth was retrieved from the Norwegian Population Registry and informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…In 2011, we conducted a sample of population-based epidemiological data on MS patients born between 1930 and 1979 in Norway retrieved from previously published population studies 23,24 and included cases not identified in the registries at the date for data extraction, as described in the previously published studies using the same cohort. 8,23,24 In addition, we included data from about 1200 patients with MS in a cohort enrolled in the Oslo Multiple Sclerosis Registry. 25 We retrieved the place of birth, sex and data on all of patients' unaffected siblings and their year of birth from the Norwegian Population Patients had been diagnosed with MS according to the criteria of Poser et al 26 or McDonald.…”
Section: Study Population and Study Designmentioning
confidence: 99%
“…In 2011, we conducted a sample of population-based epidemiological data on MS patients born between 1930 and 1979 in Norway retrieved from previously published population studies 23,24 and included cases not identified in the registries at the date for data extraction, as described in the previously published studies using the same cohort. 8,23,24 In addition, we included data from about 1200 patients with MS in a cohort enrolled in the Oslo Multiple Sclerosis Registry. 25 We retrieved the place of birth, sex and data on all of patients' unaffected siblings and their year of birth from the Norwegian Population Patients had been diagnosed with MS according to the criteria of Poser et al 26 or McDonald.…”
Section: Study Population and Study Designmentioning
confidence: 99%
“…The sex discrepancy favoring greater female MS prevalence has been slowly increasing over the 20th century 6 . Additionally, the female‐to‐male ratio has been largely driven by the youngest age groups, a category that is highly susceptible to lifestyle and hormonal changes 20 . A recent large cohort study that enrolled almost 16,000 definitive MS patients showed significant widening of the sex gap 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Magyari reported from the Danish national MS register that incidence rates for women had increased from 4.61 to 11.85 during the period 1973–2002, while the incidence for men was essentially constant . A study from Norway reported an increase in female/male ratio of 1.7 from patients born 1930–1935 to 2.6 in those born 1970–1979, mainly determined by patients with a relapsing‐remitting onset . In contrast to these results, several reports from Sweden observed no change in the female/male prevalence ratio, including a short‐term (2001–2008) study by Ahlgren et al.…”
mentioning
confidence: 90%